Tislelizumab for cervical cancer: A retrospective study and analysis of correlative blood biomarkers - Zheng, Xiaojing; Gu, Haifeng; Cao, Xinping; Pan, Baoyue; Xiang, Huiling; Ju, Mingxiu; Xu, Shijie; Zheng, Min (Frontiers in Immunology, 2023)
Background: Tislelizumab is an anti-programmed cell death 1 (PD-1) monoclonal antibody engineered to minimize binding to Fcγ receptors. It has been used to treat several solid tumors. However, its efficacy and toxicity, and the predictive and prognostic value of baseline hematological parameters in patients with recurrent or metastatic cervical cancer (R/M CC) receiving tislelizumab remain unclear. Methods: We reviewed 115 patients treated for R/M CC with tislelizumab from March 2020 to June 2022 in our institute. The antitumor activity of tislelizumab was assessed using RECIST v1.1. Associations between the baseline hematological parameters and efficacy of tislelizumab in these patients were analyzed. Results: With a median follow-up of 11.3 months (range, 2.2–28.7), the overall response rate was 39.1% (95% CI, 30.1–48.2) and the disease control rate was 77.4% (95% CI, 69.6–85.2). The median progression-free survival (PFS) was 19.6 months (95% CI, 10.7 to not reached). The median overall survival (OS) was not reached. Treatment-related adverse events (TRAEs) of any grade occurred in 81.7% of the patients and only 7.0% of the patients experienced grade 3 or 4 TRAEs. Univariate and multivariate regression analyses showed that the level of pretreatment serum C-reactive protein (CRP) was an independent risk factor for the response (complete or partial response) to tislelizumab and the PFS of R/M CC patients treated with tislelizumab (P = 0.0001 and P = 0.002, respectively). R/M CC patients with elevated baseline CRP levels had a short PFS (P = 0.0005). Additionally, the CRP-to-albumin ratio (CAR) was an independent risk factor for the PFS and OS of R/M CC patients treated with tislelizumab (P = 0.001 and P = 0.031, respectively). R/M CC patients with an elevated baseline CAR had short PFS and OS (P < 0.0001 and P = 0.0323, respectively). Conclusions: Tislelizumab showed promising antitumor activity and tolerable toxicity in patients with R/M CC. The baseline serum CRP levels and CAR showed potential for predicting the efficacy of tislelizumab and the prognosis of R/M CC patients receiving tislelizumab.